FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA BIDAN DALAM PELAYANAN NIFAS DI KOTA SALATIGA - Trianita Eka Pamundhi; Ayun Sriatmi; Sutopo Patria Jati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
In the last 3 years Salatiga city increased the increase in maternal mortality cases from 2 to 4 case. The highest deaths occurred during the second period in the puerperal service. Midwives have not been optimal in providing postpartum services obtained from preliminary survey results. The midwife does not provide services to all postpartum mothers and does not perform complete services.The purpose of this study was to analyze factors related to the performance of midwives in postpartum services. Quantitative research type with analytical method, cross sectional approach, and using Chi Square test. The sample numbered 66 midwives with an average age of 36 years, educated midwifery D3 and has had a long working period. The results showed that respondents had good appraisal on job design (53%) and coworker (50%), while having poor assessment on facilities and facilities (56.1%), supervision (37%), knowledge (53%), attitudes (53%), leadership (51.5%), motivation (51.5%). Variables related to midwife's performance in childbirth service were working period (p = 0.026), facilities and facilities (p = 0.000), supervision (p = 0.000), attitude (p = 0.000), leadership (p = 0.000), and motivation (p = 0.000). The unrelated variables were job design (p = 0.304), knowledge (p = 0.153), and coworkers (p = 0.624). The midwife are expected to increas their performance by optimizing the schedule of postpartum service, giving the completely service for all the postpartum mother. For Health Service are expected in optimizing the supervision to increase the midwife responsibility in postpartum service.